PENGARUH BIAYA PRODUKSI TERHADAP LABA BERSIH CV. BERKAH JAYA GENERAL SUPPLIER SNACK FOOD - Yaya Suharya; Sutrisno Sutrisno; Risma Nurmilah (Jurnal Bina Akuntansi, 2021)
In addition to providing goods and services, the company aims to obtain maximumprofit. As a provider of goods, the fulfillment of better product quality and competitiveprices is a challenge for the company. However, this was accompanied by highproduction costs. Thus, companies are required to be able to reduce production costswhich consist of raw material costs, direct labor wages and factory overhead. Theabove phenomenon inspires the author to examine "The Effect of Production Costs onCompany Profits" with multiple linear regression analysis. The purpose of this studywas to determine the effect of production costs on company profits CV Berkah JayaGeneral Supplier snack food. The regression analysis shows that simultaneously, rawmaterial costs, direct labor wages and factory overheads have a negative effect oncompany profits. The higher the production cost, the lower the profit the companygets. The variable that most strongly affects company profits is the cost of rawmaterials.